Interior of the Dr. Charles M. Howell house on Kent Road, 1961. - (:unkn) unknown (Forsyth County Public Library)
WSJ 1-22-61 p.C1.
Interior of the Dr. Charles M. Howell house at 1100 East Kent Road, 1961.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth